Active energy ray-polymerizable composition and article
Patent Information
- Application Number
- JP2024202393
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-03-31
AI Technical Summary
【0009】 本発明によれば、耐擦傷性に優れ、さらに被ホットスタンプ性及び耐アルコール性が良好な硬化被膜が得られる活性エネルギー線重合性組成物、及びその硬化被膜を有する物品を提供することができる。
Smart Images

Figure 2025022926000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-polymerizable composition used for forming a cured product such as a cured coating, in particular an active energy ray-polymerizable composition capable of forming a cured coating formed on the surface of a cosmetic container or the like, which is suitable for heat-pressing a foil onto the surface using a hot stamp, and an article such as a cosmetic container that is covered with a cured coating of the composition. [Background technology]
[0002] An active energy ray-polymerizable composition has the property of being polymerized and cured in a short time when irradiated with active energy rays such as ultraviolet rays. The composition is used, for example, as a material for forming a cured coating for modifying the surface of a substrate of home electrical appliances such as a mobile phone or a cosmetic container.
[0003] The cured coating obtained from the composition is required to improve the scratch resistance of the coated object, which is mainly the substrate. Furthermore, when the substrate is a cosmetic container, a hot stamp may be used to heat and press a foil onto the surface of the cured coating. In this case, the cured coating is required to have a high foil transfer rate (hot stamp resistance) and alcohol resistance to prevent corrosion caused by the contents of the cosmetic product.
[0004] For example, Patent Document 1 describes an active energy ray-polymerizable composition containing a hydroxyl group-containing (meth)acrylic polymer and a polyfunctional (meth)acrylate as an active energy ray-polymerizable composition with improved scratch resistance. Patent Document 2 describes an active energy ray-polymerizable composition having scratch resistance and hot stamp resistance.
[0005] However, the active energy ray-polymerizable composition described in Patent Document 1 does not have sufficient hot stamp resistance, and the active energy ray-polymerizable composition described in Patent Document 2 does not have sufficient alcohol resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-059166 A [Patent Document 2] JP 2019-70088 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to solve the above-mentioned problems and to provide an active energy ray-polymerizable composition which can give a cured coating film having excellent scratch resistance and good hot stamp resistance and alcohol resistance, and an article having the cured coating film. [Means for solving the problem]
[0008] The above problems are solved by the present inventions [1] to
[12] below. [1] An active energy ray-polymerizable composition comprising: a (meth)acrylic polymer (A) having a hydroxyl value of 20 mgKOH / g or less; a bifunctional (meth)acrylate (D) having a weight average molecular weight of 1,000 or less; and a photopolymerization initiator (E). [2] The active energy ray-polymerizable composition according to [1], wherein the (meth)acrylate (D) has a cyclic structure. [3] The active energy ray-polymerizable composition according to the above [1] or [2], wherein the content of the (meth)acrylic polymer (A) is 10 to 50 mass %. [4] The active energy ray-polymerizable composition according to any one of [1] to [3], wherein the content of the (meth)acrylate (D) is 10 to 50 mass %. [5] The active energy ray-polymerizable composition according to any one of [1] to [4], further comprising a urethane (meth)acrylate (B) having a weight average molecular weight of more than 1,000. [6] The active energy ray-curable polymerization composition according to [5], wherein the urethane (meth)acrylate (B) has an aromatic ring. [7] The active energy ray polymerizable composition according to the above [5] or [6], wherein the content of the urethane (meth)acrylate (B) is 1 to 40 mass %. [8] The active energy ray-polymerizable composition according to any one of the above [1] to [7], further comprising a tri- or higher functional (meth)acrylate (C) modified with alkylene oxide and / or caprolactone. [9] The active energy ray-polymerizable composition according to the above [8], wherein the content of the (meth)acrylate (C) is 30 to 85 mass %.
[10] An article, in which the surface of a substrate is covered with a cured coating formed from the active energy ray-polymerizable composition according to any one of the above [1] to [9].
[11] The article according to
[10] , wherein the article is a cosmetic container.
[12] An article comprising the cured coating of the article according to
[10] or
[11] above, and a foil attached to the surface of the cured coating. Effect of the Invention
[0009] According to the present invention, it is possible to provide an active energy ray-polymerizable composition which gives a cured coating film having excellent scratch resistance and further excellent hot stamp resistance and alcohol resistance, and an article having the cured coating film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below. In this specification, "(meth)acrylate" is a general term for "acrylate" and "methacrylate", and means one or both of these. "(meth)acryloyl group" is a general term for "acryloyl group" and "methacryloyl group", and means one or both of these. "(meth)acrylic acid" is a general term for "acrylic acid" and "methacrylic acid", and means one or both of these. "(meth)acrylic polymer" is a general term for "acrylic polymer" and "methacrylic polymer", and means one or both of these. "(meth)acrylic monomer" is a general term for "acrylic monomer" and "methacrylic monomer", and means one or both of these.
[0011] [Active energy ray polymerizable composition] The active energy ray-polymerizable composition of the present invention (hereinafter referred to as "the composition") contains a (meth)acrylic polymer (A) (hereinafter referred to as "component (A)") having a hydroxyl value of 20 mgKOH / g or less, a bifunctional (meth)acrylate (D) (hereinafter referred to as "component (D)") having a weight-average molecular weight of 1,000 or less, and a photopolymerization initiator (E) (hereinafter referred to as "component (E)").
[0012] [Component (A)] The present composition contains component (A), a (meth)acrylic polymer (A) having a hydroxyl value of 20 mgKOH / g or less. A (meth)acrylic polymer is a polymer containing structural units derived from a (meth)acrylic monomer. Component (A) is a component that contributes to improving the curability of the present composition, as well as the transparency and alcohol resistance of a cured product, such as a cured coating, of the present composition.
[0013] The component (A) can be produced by polymerizing a monomer mixture containing a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, i-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxypropyl (meth)acrylate. Examples of the hydroxyl group-containing (meth)acrylic acid esters include hydroxypropyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; aromatic ring-containing (meth)acrylic acid esters include phenoxy (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate and o-biphenyloxyethyl (meth)acrylate; glycidyl group-containing (meth)acrylic acid esters include glycidyl (meth)acrylate; isocyanate group-containing (meth)acrylic acid esters include (meth)acrylic isocyanate and 2-(meth)acryloyloxyethyl isocyanate; (meth)acrylic acids such as acrylic acid and methacrylic acid; and (meth)acrylic acid salts such as ammonium (meth)acrylate, sodium (meth)acrylate and potassium (meth)acrylate. The component (A) preferably contains a structural unit derived from (meth)acrylic acid, in that this improves hot stampability.
[0014] The component (A) may contain a structural unit derived from a monomer other than the (meth)acrylic monomer. Examples of the monomer other than the (meth)acrylic monomer include a monomer having a double bond. Specific examples include aromatic vinyls such as styrene and α-methylstyrene; vinyl carboxylates such as vinyl acetate and vinyl propionate; unsaturated dicarboxylic acids such as maleic anhydride, itaconic acid, and fumaric acid; and N-vinyl lactams such as N-vinylpyrrolidone and N-vinylcaprolactam. The structural units of the component (A) may be of one type, or two or more types.
[0015] The component (A) can be produced by polymerizing the raw material monomers by a known method, for example, a solution polymerization method using an azo-based initiator, or a photopolymerization method using an acylphosphine oxide-based initiator.
[0016] The hydroxyl value of component (A) is preferably 0 to 10 mgKOH / g, more preferably 0 to 5 mgKOH / g. The lower the hydroxyl value, the more the cured coating tends to have improved hot stampability, alcohol resistance, adhesion to substrates, and coating workability. The hydroxyl value of the polymer can be measured by titration as a potassium hydroxide equivalent value. The hydroxyl value of the component (A) can be adjusted, for example, by the copolymerization ratio of a hydroxyl group-containing monomer such as a hydroxyl group-containing (meth)acrylic acid ester.
[0017] The weight average molecular weight (hereinafter referred to as "Mw") of component (A) is preferably from 1,000 to 100,000, more preferably from 10,000 to 90,000, and even more preferably from 20,000 to 80,000, from the standpoints of the hot stampability, alcohol resistance, and adhesion to substrates of the cured coating, as well as coating workability. Mw can be adjusted by controlling the polymerization conditions when polymerizing component (A), such as the type and amount of polymerization initiator, the type and amount of solvent, reaction temperature, reaction time, etc. In this specification, the term "weight average molecular weight" refers to the polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography.
[0018] The component (A) in the present composition may be one type or two or more types. The content of component (A) is preferably from 10 to 50 mass %, more preferably from 10 to 30 mass %, from the standpoints of the hot stampability, alcohol resistance, and adhesion to substrates of the cured coating, as well as coating workability.
[0019] [(D) component] The composition contains component (D), a bifunctional (meth)acrylate (D) having a weight average molecular weight of 1000 or less. Component (D) is a component that contributes to the hot stamp resistance of the cured coating. Examples of component D include a compound (D1) having a cyclic skeleton between two (meth)acryloyloxy groups (hereinafter referred to as "component (D1)") and a compound (D2) having a linear structure between the two (meth)acryloyloxy groups (hereinafter referred to as "component (D2)").
[0020] Examples of the component (D1) include di(meth)acrylates having an aromatic ring skeleton, such as bisphenol A di(meth)acrylate and bisphenol F di(meth)acrylate; di(meth)acrylates having an alicyclic skeleton, such as 1,4-cyclohexanediol di(meth)acrylate, tricyclodecanediyldimethylene di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate and dimethyloltricyclodecane di(meth)acrylate; and polyalkylene oxide adducts, polycaprolactone adducts, and polycarbonate adducts of these di(meth)acrylates.
[0021] Examples of the component (D2) include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, glycerol 1,3-di(meth)acrylate, neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, neopentyl glycol hydroxypivalate di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polycarbonate di(meth)acrylate, and polyalkylene oxide adducts, polycaprolactone adducts, and polycarbonate adducts of these di(meth)acrylates.
[0022] As the (D) component, from the viewpoint of the scratch resistance of the cured coating, the (D1) component is preferred, a di(meth)acrylate having a bisphenol A skeleton and a di(meth)acrylate having tricyclodecane are more preferred, and bisphenol A (EO)4 diacrylate and dimethylol tricyclodecane diacrylate are even more preferred.
[0023] The component (D) in the present composition may be one type, or two or more types. The content of component (D) is preferably 1 to 70 mass%, more preferably 10 to 50 mass%. A higher content tends to improve the hot stampability of the cured coating, while a lower content tends to improve the alcohol resistance of the cured coating.
[0024] [(E) component] The present composition contains a photopolymerization initiator (E) which polymerizes and cures the present composition when irradiated with active energy rays such as ultraviolet rays. Examples of the (E) component include carbonyl compounds such as benzoin, benzoin monomethyl ether, benzoin isopropyl ether, acetoin, benzil, benzophenone, p-methoxybenzophenone, diethoxyacetophenone, benzil dimethyl ketal, 2,2-diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, methylphenyl glyoxylate, ethylphenyl glyoxylate, 2-hydroxy-2-methyl-1-phenylpropan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one; sulfur compounds such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; and acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. As the component (D), 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-2-methyl-1-phenylpropan-1-one are preferred because they are able to impart high transmittance to the cured coating of the composition.
[0025] The component (E) in the present composition may be one type, or two or more types. The content of component (E) is preferably 0.1 to 10 mass %. A higher content tends to improve the scratch resistance of the cured coating, while a lower content tends to improve the flex resistance and hot stamp resistance of the cured coating.
[0026] [Component (F)] The composition may contain a solvent (F) (hereinafter referred to as "component (F)"). Examples of component (F) include hydrocarbon solvents such as n-hexane, n-heptane, n-octane, cyclohexane, and cyclopentane; aromatic solvents such as toluene, xylene, and ethylbenzene; alcohol solvents such as methanol, ethanol, n-butanol, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, n-butyl acetate, n-amyl acetate, ethylene glycol monomethyl ether acetate, and propylene glycol monomethyl ether acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl n-amyl ketone, and cyclohexanone; ethylene glycol solvents such as diethylene glycol dimethyl ether and diethylene glycol dibutyl ether; ether solvents such as 1,2-dimethoxyethane, tetrahydrofuran, and dioxane; amide solvents such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; and carbonate solvents such as ethylene carbonate.
[0027] The component (F) in the present composition may be one type, or two or more types. The content of the (F) component is preferably 30 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the total amount of components having a polymerizable double bond, from the viewpoints of improving coating workability and leveling properties and reducing VOC emissions.
[0028] [(B) Component] The present composition may contain a urethane (meth)acrylate (B) (hereinafter referred to as "component (B)"). However, component (B) is a compound other than component (D). Component (B) is a component that contributes to the flex resistance and abrasion resistance of the cured coating film. An example of the (B) component is a urethane poly(meth)acrylate that can be synthesized from a raw material containing a polyisocyanate (b1) (hereinafter referred to as the "b1 raw material") and a (meth)acrylate (b3) having only one hydroxyl group (hereinafter referred to as the "b3 raw material"). As the (B) component, a urethane poly(meth)acrylate obtained by reacting the b1 raw material with a polyol (b2) (hereinafter referred to as the "b2 raw material") and then reacting the b3 raw material is preferred, since this can further improve the flex resistance of the cured coating.
[0029] (b1 raw material) Examples of the b1 raw material include diisocyanates such as tolylene diisocyanate, methylcyclohexane diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, dimer acid diisocyanate, and trimethylhexamethylene diisocyanate; and triisocyanates such as lysine triisocyanate. In addition, as the b1 raw material, polyisocyanates obtained by reacting polyisocyanates such as the above-mentioned diisocyanates and triisocyanates with compounds having two or more active hydrogen atoms such as amino groups, hydroxyl groups, carboxyl groups, water, etc., or polyisocyanates such as dimers to pentamers of polyisocyanates such as the above-mentioned diisocyanates and triisocyanates can also be used. As the b1 raw material, diisocyanates are preferred because the viscosity of the resulting component (B) is low, improving the coating workability of the composition and improving the flex resistance of the cured coating. Among these, isophorone diisocyanate and dicyclohexylmethane diisocyanate are more preferred. When producing component (B), the b1 raw material may be a single type of compound, or two or more types may be used in combination.
[0030] (b2 raw material) Examples of the b2 raw material include diols such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, methylpentanediol, 2,4-diethylpentanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydroxypivalic acid neopentyl glycol ester, 1,4-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, cyclohexanediol, bisphenol A, and spiroglycol; triols such as trimethylolpropane and glycerol; and polyols such as tetraols such as pentaerythritol. As the b2 raw material, there can be used polyalkylene polyols obtained by adding alkylene oxides to the above-mentioned polyols, polycaprolactone polyols obtained by adding lactones such as ε-caprolactone to the above-mentioned polyols, and polycarbonate polyols obtained by an ester exchange reaction between the above-mentioned polyols and carbonates such as alkylene carbonates, dialkyl carbonates, diaryl carbonates, and the like. As the raw material b2, diols are preferred from the viewpoint of improving the flex resistance of the cured coating of the present composition, and among them, diols containing an aromatic ring such as bisphenol A are more preferred. When producing component (B), the raw material b2 may be a single type of compound, or two or more types may be used in combination.
[0031] (b3 raw material) Examples of the b3 raw material include monohydroxyalkyl (meth)acrylate, caprolactone-modified or alkylene oxide-modified monohydroxyalkyl (meth)acrylate, and an addition reaction product of a monoepoxy compound and (meth)acrylic acid. Examples of monohydroxyalkyl (meth)acrylates include monohydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, etc. The number of carbon atoms in the hydroxyalkyl group of the monohydroxyalkyl (meth)acrylate is preferably 1 to 10.
[0032] Examples of the monohydroxyalkyl(meth)acrylate include monohydroxyalkyl poly(meth)acrylates such as glycerol acrylate methacrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate. Examples of the caprolactone-modified monohydroxyalkyl (meth)acrylate include caprolactone-modified products such as γ-caprolactone, δ-caprolactone, and ε-caprolactone.
[0033] Examples of the alkylene oxide modified monohydroxyalkyl (meth)acrylate include alkylene oxide modified products such as ethylene oxide, propylene oxide, and butylene oxide. Examples of the addition reaction product of a monoepoxy compound with (meth)acrylic acid include addition reaction products of a monoepoxy compound such as butyl glycidyl ether, 2-ethylhexyl glycidyl ether, and glycidyl (meth)acrylate with (meth)acrylic acid. As the b3 raw material, a monohydroxyalkyl mono(meth)acrylate having a hydroxyalkyl group of 2 to 4 carbon atoms is preferred, and 2-hydroxyethyl (meth)acrylate is more preferred, because the viscosity of the resulting component (B) is low and the coating workability of the composition is improved.
[0034] As a method for synthesizing the (B) component from the b1 raw material and the b3 raw material, for example, a method in which the b3 raw material is dropped into a mixture of the b1 raw material and a catalyst such as dibutyltin dilaurate heated to 30 to 90°C over 1 to 3 hours, and then reacted for another 1 to 3 hours, can be mentioned. The amounts of the b1 raw material and the b3 raw material used for synthesizing the (B) component are preferably set so that (total number of isocyanate groups in the b1 raw material) / (total number of hydroxyl groups in the b3 raw material) is 0.5 to 1.0, more preferably 0.9 to 1.0. The higher this ratio, the better the adhesion of the cured coating to the substrate, and the lower this ratio, the higher the reaction rate of the isocyanate groups, so that the storage stability of the composition tends to improve.
[0035] In addition, as a method for synthesizing the (B) component from the b1 raw material, the b2 raw material, and the b3 raw material, there may be mentioned a conventionally known method, for example, a method in which the b2 raw material is dropped into a mixture of the b1 raw material and a catalyst such as dibutyltin dilaurate heated to 30 to 90°C over 2 to 6 hours, reacted for another 1 to 3 hours, and then the b3 raw material is dropped over 1 to 3 hours, and reacted for another 1 to 3 hours. The amounts of the b1 raw material, the b2 raw material, and the b3 raw material used for synthesizing the (B) component are preferably set so that (total number of isocyanate groups in the b1 raw material) / (total number of hydroxyl groups in the b2 raw material and the b3 raw material) is 0.5 to 1.0, more preferably 0.9 to 1.0. The higher this ratio, the better the adhesion of the cured coating to the substrate, and the lower this ratio, the higher the reaction rate of the isocyanate group, so that the storage stability of the composition tends to improve.
[0036] The weight average molecular weight of component (B) is preferably from 500 to 40,000, and more preferably from 2,000 to 20,000, from the viewpoints of providing the composition with a viscosity suitable for coating work and of providing a cured coating with good flex resistance.
[0037] The component (B) in the present composition may be one type or two or more types. The content of the (B) component is preferably from 1 to 40 mass %, and more preferably from 10 to 40 mass %, from the viewpoint of the bending resistance and abrasion resistance of the cured coating.
[0038] [(C) component] The composition may contain an alkylene oxide-modified or caprolactone-modified tri- or higher functional (meth)acrylate (C) (hereinafter referred to as "component (C)"). Component (C) is a compound other than components (A) and (B). Component (C) is a component that contributes to the scratch resistance and hot stamp resistance of the cured coating.
[0039] As the component (C), a modified product obtained by modifying the following trifunctional or higher functional (meth)acrylates with alkylene oxide or caprolactone can be used. Examples of the trifunctional or higher functional (meth)acrylates include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, polyurethane tri(meth)acrylate, polyepoxy tri(meth)acrylate, and polyester tri(meth)acrylate; tetra(meth)acrylates such as ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, polyepoxy tetra(meth)acrylate, and polyester tetra(meth)acrylate; dipentaerythritol tetra(meth)acrylate, and polyepoxy tetra(meth)acrylate; Examples of the poly(meth)acrylate include penta(meth)acrylates such as thritol penta(meth)acrylate and tripentaerythritol penta(meth)acrylate; hexa(meth)acrylates such as dipentaerythritol hexa(meth)acrylate and tripentaerythritol hexa(meth)acrylate; hepta(meth)acrylate or more functional poly(meth)acrylates such as tripentaerythritol hepta(meth)acrylate and tripentaerythritol octa(meth)acrylate; trifunctional or more functional polyepoxy poly(meth)acrylates; and trifunctional or more functional polyester poly(meth)acrylates. As component (C), it is preferable to contain caprolactone-modified dipentaerythritol hexa(meth)acrylate, since this can impart high scratch resistance to the cured coating of the composition.
[0040] The component (C) in the present composition may be one type or two or more types. The content of component (C) is preferably from 30 to 85 mass %, and more preferably from 40 to 85 mass %, from the viewpoints of the scratch resistance and hot stamp resistance of the cured coating.
[0041] [(G) component] The present composition may contain another polymerizable component (G) (hereinafter referred to as "component (G)") having a polymerizable group other than components (A), (B), (C) and (D) for the purpose of improving abrasion resistance, etc. As the other polymerizable component, a (meth)acryloyl group-containing monomer is preferable. As the (meth)acryloyl group-containing monomer, for example, monofunctional (meth)acrylate, trifunctional (meth)acrylate, tetrafunctional or higher (meth)acrylate, (meth)acrylamide can be mentioned.
[0042] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, benzyl (meth)acrylate, and cresol (meth)acrylate. Examples of the acrylates include dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, 7-amino-3,7-dimethyloctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl diethylene glycol (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, lauryl (meth)acrylate, polyepoxy mono(meth)acrylate, and polyester mono(meth)acrylate.
[0043] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, polyepoxy tri(meth)acrylate, and polyester tri(meth)acrylate.
[0044] Examples of the tetrafunctional or higher (meth)acrylates include tetrafunctional (meth)acrylates such as ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, polyepoxy tetra(meth)acrylate, and polyester tetra(meth)acrylate; pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate and tripentaerythritol penta(meth)acrylate; hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate and tripentaerythritol hexa(meth)acrylate; heptafunctional or higher (meth)acrylates such as octa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate; tetrafunctional or higher polyepoxy poly(meth)acrylates; and tetrafunctional or higher polyester poly(meth)acrylates.
[0045] Examples of (meth)acrylamides include (meth)acrylamide, isobutoxymethyl(meth)acrylamide, t-octyl(meth)acrylamide, and diacetone(meth)acrylamide.
[0046] The composition may contain one type of component (G) or two or more types of components. The content of component (G) is preferably from 0.1 to 10 mass %, more preferably from 1 to 5 mass %.
[0047] [Other ingredients] The composition may contain components other than the above-mentioned components (A) to (G) (hereinafter referred to as "other components"), such as sensitizers, dispersants, waxes, light stabilizers, antioxidants, surface conditioners, antifoaming agents, heat stabilizers, antistatic agents, antifogging agents, polymers other than component (A), fine particles, thixotropic agents, and coupling agents.
[0048] Sensitizers include, for example, benzoin isopropyl ether and thioxanthone. Examples of dispersants include Anti-Terra-U, Anti-Terra-203 / 204, Disperbyk-101, 107, 110, 111, 130, 161, 162, 163, 164, 165, 166, 170, 400, Bykumen, BYK-P104, P105, P104S, 240S, and Lactimon (all of which are trade names) manufactured by BYK Chemie.
[0049] Examples of the wax include polyamide wax and oxidized polyethylene wax. Examples of the light stabilizer include hindered amines such as bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, and bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate.
[0050] Antioxidants include, for example, hindered phenols, organic phosphites and organic phosphonites.
[0051] Examples of the surface conditioner include a silicone-based leveling agent, an acrylic-based leveling agent, a fluorine-based leveling agent, and a vinyl-based leveling agent.
[0052] Examples of the defoaming agent include non-silicone-based defoaming agents such as polysiloxane, polysiloxane-based defoaming agents such as fluorine-modified polysiloxane, acrylic acid-based defoaming agents such as copolymers of alkyl methacrylate, acrylate and acrylic acid, butadiene copolymer-based defoaming agents, and mineral oil-based defoaming agents.
[0053] Heat stabilizers include, for example, triphenyl phosphite, tris(2,6-dimethylphenyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, a mixture of tris(mono-nonylphenyl)phosphite and tris(di-nonylphenyl)phosphite, dimethylbenzenephosphonate, and trimethyl phosphate. Antistatic agents include, for example, glycerol monostearate, sodium stearyl sulfonate, and sodium dodecylbenzenesulfonate.
[0054] Anti-fogging agents include, for example, glycerol-1-methacryloyloxyethyl urethane and glycerol-1-methacryloyloxypropyl urethane. Examples of polymers other than component (A) include (meth)acrylic polymers, (meth)acrylonitrile polymers, butadiene polymers, urethane polymers, polyester polymers, polyamide polymers, polyamideimide polymers, and phenol polymers.
[0055] Examples of the fine particles include organic fillers such as acrylic beads and urethane beads, inorganic fillers such as silica and titanium, and inorganic fillers that have been surface-organized with a silane coupling agent. Methods for blending the fine particles into the present composition include blending the fine particles in a pre-dispersed state, and blending the fine particles into the present composition and then dispersing them using a three-roll mill or a dyno mill. In order to improve dispersibility, dispersants such as carboxylic acid-based, polycarboxylic acid-based, and polyacrylic acid-based can also be used in combination.
[0056] Examples of the thixotropic agent include organic thixotropic agents such as amide-based, polyethylene oxide-based, and hydrogenated castor oil-based agents; and inorganic thixotropic agents such as silica, bentonite, and organic silane coupling-treated products thereof, and surface-treated calcium carbonate. Examples of the coupling agent include silane coupling agents and titanium coupling agents to which functional groups such as (meth)acryloyloxy groups, vinyl groups, epoxy groups, and amino groups have been added.
[0057] [Method of manufacturing the present composition] The composition can be produced, for example, by mixing components (D), (E), and (F) with component (A) which has been previously polymerized by a method such as suspension polymerization or photopolymerization, and then mixing components (B), (C), (G) and other components as necessary. The order and procedure for mixing the components are not particularly limited and can be selected appropriately.
[0058] [Goods] The present composition can be used to coat the surface of various substrates such as paper, various molded articles such as polymers, etc. The article of the present invention is one in which the surface of a substrate is coated with a cured coating formed from the present composition. Examples of polymer molded products that can be used as substrates include sheet-shaped molded products, film-shaped molded products, and injection molded products of various shapes obtained by injection molding. Examples of polymer types include polymethyl methacrylate polymers, polycarbonate polymers, polyester polymers, polyester carbonate polymers, polystyrene polymers, acrylonitrile-butadiene-styrene polymers (hereinafter referred to as "ABS"), acrylonitrile-styrene polymers, polyamide polymers, polyarylate polymers, polymethacrylimide polymers, and polyallyl diglycol carbonate polymers. Specific examples of substrates include cosmetic containers, in which foil is often heat-pressed onto the surface of a cured coating using a hot stamp.
[0059] The article of the present invention can be produced, for example, by applying the present composition to the surface of a substrate and then irradiating the resulting coating with active energy rays to form a cured coating. The composition can be applied to a substrate by, for example, brush coating, spray coating, dip coating, spin coating, curtain coating, bar coating, or other methods. When applying, the composition may be heated or diluted with a subcritical fluid to adjust the viscosity. From the viewpoint of the curability of the composition and the abrasion resistance of the cured coating, the coating of the composition is preferably applied so that the thickness of the cured coating is 0.001 mm or more and 0.1 mm or less, more preferably 0.002 mm or more and 0.05 mm or less, and even more preferably 0.004 mm or more and 0.03 mm or less.
[0060] Examples of the active energy rays irradiated to the coating film of the composition include α-rays, β-rays, γ-rays, and ultraviolet rays. From the viewpoint of versatility, ultraviolet rays are preferred as the active energy rays. Examples of ultraviolet ray sources include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, metal halide lamps, magnetron-based electrodeless UV lamps, and LEDs.
[0061] Examples of the atmosphere when irradiating with active energy rays include inert gases such as nitrogen and argon, and air. From the viewpoints of practicality and economy, air is preferred as the atmosphere. Preferred curing conditions when using ultraviolet rays as active energy rays include, for example, a high-pressure mercury lamp with an integrated light amount of 100 to 3000 mJ / cm at a wavelength of 340 to 380 nm. 2 An example of such a method is irradiation so that the
[0062] A preferred embodiment of the article of the present invention is an article having a foil attached to the surface of the cured coating of the article of the present invention. The cured coating obtained from the present composition has a high foil transfer rate, so the article of the present invention is suitable for a cosmetic container, the surface of which is often printed by hot stamping. A high foil transfer rate can minimize printing costs, so the transfer rate is preferably 60% or more, more preferably 80% or more, even more preferably 90% or more, and most preferably 100%. The foil transfer rate can be determined by the method described in the Examples below. EXAMPLES
[0063] The present invention will now be described with reference to examples and comparative examples. In the following description, "parts" means parts by mass.
[0064] (1) Preparation of evaluation samples The active energy ray-polymerizable composition was spray-coated on an ABS plate (thickness: 3 mm, size: 10 cm x 10 cm) so that the thickness of the cured film was 0.02 mm. The substrate with the coating was then heated in an oven at 60°C for 3 minutes to volatilize the organic solvent. Further, using a high-pressure mercury lamp in air, the active energy ray-polymerizable composition was spray-coated on an ABS plate (thickness: 3 mm, size: 10 cm x 10 cm) so that the thickness of the cured film was 0.02 mm. 2 , the cumulative light intensity is 1000mJ / cm 2 The ABS plate was then irradiated with ultraviolet light of 1000 nm to prepare an ABS plate with a hardened coating for use in the following evaluations.
[0065] (2) Evaluation of hot stampability A 2 cm square rubber stamp attached to a Leather Tools foil stamping machine was heated to 150°C, and a KURZ hot stamp foil (product name: 4PT) was pressed against the cured coating surface of the evaluation sample prepared in (1) for 1 second, and the area where the hot stamp foil was transferred was measured. The transfer rate was calculated using the following formula. Transfer rate (%) = area (cm2) of hot stamp foil transferred 2 )×100 / Engraving area(4cm 2 ) The hot stampability was evaluated based on the calculated transfer rate according to the following criteria. <Evaluation Criteria for Hot Stampability> A: Transfer rate is 60% or more B: Transfer rate is 30% or more and less than 60% C: Transfer rate is less than 30%
[0066] (3) Evaluation of Abrasion Resistance The cured film surface of the evaluation sample prepared in (1) was rubbed with steel wool #000 manufactured by BONSTER SALES, attached to a flat friction tester of a coating tester, under the condition of a load of 250 g / cm 2 , for 50 reciprocations. The haze values before and after rubbing were measured according to JIS-K7105 using a haze meter HM-65W manufactured by Murakami Color Technology Research Institute, and the haze increase value was obtained. The abrasion resistance was evaluated based on the following criteria from the haze increase value. <Evaluation Criteria for Abrasion Resistance> A: Haze increase value is less than 2% B: Haze increase value is 2% or more and less than 4% C: Haze increase value is 4% or more
[0067] (4) Evaluation of Alcohol Resistance The evaluation sample prepared in (1) was immersed in a 50% ethanol solution adjusted to 40°C for 24 hours, then taken out and air-dried, and the appearance of the cured film surface was visually observed. The alcohol resistance was evaluated based on the following criteria from the area of defective parts where wrinkles, peeling, discoloration, etc. were observed. <Evaluation Criteria for Alcohol Resistance> A: No defective parts B: Defective parts are more than 0% and 20% or less of the entire cured film C: Defective parts are more than 20% of the entire cured film
[0068] (5) Measurement of Weight-Average Molecular Weight The weight-average molecular weight (Mw) was measured under the following conditions using a GPC (Gel Permeation Chromatography) system (manufactured by Tosoh Corporation, product name: HLC-8220GPC). <GPC Measurement Conditions> Columns: "TSK-gel superHZM-M", "TSK-gel HZM-M", "TSK-gel HZ2000" Eluent:THF Flow rate: 0.35mL / min Injection volume: 10μL Column temperature: 40℃ Detector: UV-8020
[0069] [Production Example 1] Production of polymer (A1) 75 parts of toluene was placed in a 5-liter four-neck flask equipped with a stirrer and heated to 90°C. Then, under nitrogen bubbling, 55.4 parts of methyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester M), 22.3 parts of i-butyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester B), 22.3 parts of dicyclopentanyl methacrylate (manufactured by Hitachi Chemical, trade name: FA-513M), and 0.3 parts of azobisisobutyronitrile (manufactured by Otsuka Chemical, trade name: AIBN) were added dropwise over 4 hours. Then, 0.05 parts, 0.1 parts, 0.1 parts, and 0.2 parts of azobisisobutyronitrile were added every 45 minutes. The mixture was heated to 98°C and held for 2 hours, and then toluene and xylene were added to obtain a (meth)acrylic polymer (A1) (hereinafter referred to as "polymer (A1)") solution with a non-volatile content of 40% by mass. The hydroxyl value and Mw of the polymer (A1) calculated from the composition of the raw materials used were 0 mgKOH / g and 59,000, respectively.
[0070] [Production Example 2] Production of Comparative Polymer (X1) In a 5-liter four-neck flask equipped with a stirrer, 60 parts of butyl acetate (manufactured by KH Neochem) were placed and heated to 120°C. Then, under nitrogen bubbling, 51.75 parts of methyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester M), 29 parts of n-butyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester B), 19 parts of 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester HO), 0.25 parts of acrylic acid (manufactured by Mitsubishi Chemical), and 2.5 parts of 2'-azobis-2-methylbutyronitrile (manufactured by Otsuka Chemical, trade name: AMBN) were added dropwise over a period of 4 hours. This mixture was kept at 120°C for 1 hour, and then 0.1 parts of 2'-azobis-2-methylbutyronitrile was added. After further maintaining this at 120°C for 1 hour, the temperature was lowered to 70°C over 1 hour, and 40 parts of ethyl acetate (manufactured by Daicel) was added to obtain a solution of a hydroxyl-containing (meth)acrylic polymer (X1) (hereinafter referred to as "polymer (X1)") with a non-volatile content of 50% by mass. The hydroxyl value of polymer (X1) calculated from the charged composition of the raw materials was 82 mgKOH / g, and Mw was 10,000.
[0071] [Production Example 3] Production of Comparative Polymer (X2) In a 5-liter four-neck flask equipped with a stirrer, 85 parts of butyl acetate (manufactured by KH Neochem) were placed and heated to 110°C. Then, under nitrogen bubbling, 48 parts of methyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester M), 35.4 parts of n-butyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester B), 11 parts of n-butyl acrylate (manufactured by Mitsubishi Chemical, trade name: butyl acrylate), 5.1 parts of 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical, trade name: Acryester HO), 0.5 parts of acrylic acid (manufactured by Mitsubishi Chemical), and 0.6 parts of azobisisobutyronitrile (manufactured by Otsuka Chemical, trade name: AIBN) were added dropwise over 4 hours. This mixture was kept at 110°C for 1 hour, and then 0.5 parts of azobisisobutyronitrile was added. After further maintaining this at 110°C for 2 hours, 15 parts of butyl acetate was added to obtain a solution of a (meth)acrylic polymer having a hydroxyl group (hereinafter referred to as "polymer (X2)") with a non-volatile content of 50% by mass. The hydroxyl value of polymer (X2) calculated from the charged composition of the raw materials was 22 mgKOH / g, and Mw was 26,000.
[0072] [Production Example 4] Production of urethane acrylate (B1) In a 5-liter four-neck flask equipped with a stirrer, 261.6 parts of bisphenol A-containing diol (ADEKA, trade name: Adeka Polyether BPX-11), 19.1 parts of neopentyl glycol (Mitsubishi Gas Chemical), 0.18 parts of dibutyltin dilaurate (ADEKA, trade name: Adeka Stab BT-11), 1.46 parts of di-t-butyl-p-cresol (Honshu Chemical Industry, trade name: H-BHT), and 224 parts of butyl acetate (KH Neochem) were placed and heated to 60°C. 400 parts of isophorone diisocyanate (Sumika Bayer Urethane, trade name: Desmodur I) were added dropwise over 4 hours. After the mixture was held at 60°C for 1 hour, 217 parts of 2-hydroxyethyl acrylate (Osaka Organic Chemical Industry, trade name: HEA) were added dropwise while heating to 70°C over 2 hours. After the mixture was kept at 70° C. for 1 hour, 0.1 parts of dibutyltin dilaurate was added and the mixture was further kept at 70° C. for 5 hours to obtain urethane acrylate (B1). The Mw of the urethane acrylate (B1) was 4,300.
[0073] [Examples 1 to 3 and Comparative Examples 1 to 4] An active energy ray-polymerizable composition was prepared according to the formulation shown in Table 1, and various evaluations were carried out. The evaluation results are shown in Table 1.
[0074] [Table 1]
[0075] The abbreviations in Table 1 are as follows: A1: Polymer (A1) solution produced in Production Example 1 X1: Polymer (X1) solution prepared in Preparation Example 2 X2: Polymer (X2) solution prepared in Preparation Example 3 B1: Urethane acrylate (B1) produced in Production Example 4 DPCA-20: Caprolactone 2mol modified dipentaerythritol hexaacrylate (manufactured by Nippon Kayaku, product name: DPCA-20) DPCA-60: Caprolactone 6mol modified dipentaerythritol hexaacrylate (manufactured by Nippon Kayaku, product name: DPCA-60) A-BPE-4: Bisphenol A (EO) 4 diacrylate (manufactured by MIWON, product name: Miramar M240) DCPA: Dimethyloltricyclodecane diacrylate (manufactured by Kyoei Chemical, product name: Light Acrylate DCP-A) M216: Neopentyl glycol (PO)2 diacrylate (manufactured by MIWON, product name: Miramar M216) HCPK: 1-hydroxycyclohexyl phenyl ketone (manufactured by IGM, trade name: Omnirad184) PGM: Propylene glycol monomethyl ether (manufactured by Daicel, product name: Methoxypropanol) DIBK: Diisobutyl ketone (manufactured by KH Neochem, product name: DIBK) Paintad M: Silicone polyether copolymer (manufactured by Toray Dow Corning, product name: Paintad M)
[0076] It is clear from Table 1 that the cured coatings of the active energy ray-polymerizable compositions prepared in Examples 1 to 3 have good hot stamp resistance, scratch resistance, and alcohol resistance. On the other hand, the active energy ray-polymerizable composition prepared in Comparative Example 1 did not contain the component (A), and therefore the alcohol resistance of the cured coating was poor. The active energy ray-polymerizable compositions of Comparative Examples 2 and 3 did not contain the component (D), and therefore the hot stamp resistance and alcohol resistance of the cured coating were poor. The active energy ray-polymerizable composition of Comparative Example 4 did not contain the components (A) and (D), and therefore the hot stamp resistance and alcohol resistance of the cured coating were poor. [Industrial Applicability]
[0077] The active energy ray-polymerizable composition of the present invention can form a cured coating film that has excellent scratch resistance and further has good hot stamp resistance and alcohol resistance, and therefore can be suitably used for applications such as cosmetic containers in which a foil is heated and pressed onto the surface of the cured coating film using a hot stamp.
Claims
1. The composition comprises a (meth)acrylic polymer (A) having a hydroxyl value of 20 mgKOH / g or less, a urethane (meth)acrylate (B) having a weight average molecular weight of more than 1000, a tri- or higher functional (meth)acrylate modified with alkylene oxide and / or caprolactone (C), a bifunctional (meth)acrylate (D) having a weight average molecular weight of 1000 or less, and a photopolymerization initiator (E), The component (A) contains methyl (meth)acrylate and a monomer having an alicyclic skeleton, the component (D) is a compound (D1) having a cyclic skeleton between two (meth)acryloyloxy groups or a compound (D2) having a linear structure between the two (meth)acryloyloxy groups, Coating the surface of a polymeric substrate; An active energy ray polymerizable composition.
2. 2. The active energy ray-polymerizable composition according to claim 1, wherein the content of the (meth)acrylic polymer (A) is 10 to 50 mass %.
3. 3. The active energy ray-polymerizable composition according to claim 1, wherein the content of the (meth)acrylate (D) is 10 to 50 mass %.
4. The active energy ray-curable polymerizable composition according to any one of claims 1 to 3, wherein the urethane (meth)acrylate (B) has an aromatic ring.
5. The active energy ray polymerizable composition according to any one of claims 1 to 4, wherein the content of the urethane (meth)acrylate (B) is 1 to 40 mass%.
6. The active energy ray polymerizable composition according to any one of claims 1 to 5, wherein the content of the (meth)acrylate (C) is 30 to 85 mass%.
7. An article, comprising a polymer substrate having a surface coated with a cured coating formed from the active energy ray-polymerizable composition according to any one of claims 1 to 6.
8. The article of claim 7, wherein the article is a cosmetic container.
9. 9. An article comprising a foil adhered to the surface of the cured coating of the article according to claim 7 or 8.
Citation Information
Patent Citations
Image forming material and image forming method
JP1995306527A
Photocurable coating material composition for woody material
JP2005255816A
Optical filter and method of manufacturing the same
JP2010118396A
Optical film having antistatic layer, polarizing plate and image display device
JP2011053493A
Photosensitive resin composition, photosensitive element and permanent mask resist
JP2011170197A